Emotion-based themes and locutions in Ahmed Yerima’s Otaelo - Joshua Oladepo Olatundun (Universitas Ahmad Dahlan, 2023)
This study investigates locutionary indexing of emotion-based themes using Ahmed Yerima’s Otaelo as our selected text. Ahmed Yerima’s Otaelo has a considerable volume of pragmatically salient emotional themes. Aspects of the theories of speech acts, modified Odebunmi’s adapted model of pragmeme and emotionology, considered capable of addressing linguistic forms and functions and expression of emotion were adopted. The findings revealed that themes of emotional satisfaction and perturbation are found in Otaelo. Emotional satisfaction, incorporating love, assurance, appreciation and admiration, are indexed in the text. Emotional perturbation covers fear, anger, rejection, deception, conflict, disparagement and regret. The paper concludes that Ahmed Yerima’s Otaelo thematised emotional satisfaction and perturbation through salient locutions, thereby contributing to the increasing works on pragmatics.